Which are the options and dosages for clobazam shortages on epilepsy treatment? Review of literature and survey of specialists - Pinto, Lécio Figueira; Mendonça, Guilherme Simone; Guerreiro, Carlos Alberto Mantovani (Arquivos de Neuro-Psiquiatria, 2025)
Clobazam (CLB) has been an established treatment for epilepsy since the 1970s, with a broad spectrum. It is frequently used as add on therapy for refractory patients. Furthermore, it is different from classic benzodiazepines (BZD) for containing nitrogen atoms in 1 and 5 positions of B ring (other are 1.4-BZD). This explains why CLB has a better tolerability and a lower chance of causing sedation, being an excellent option for epilepsy treatment compared with other BZDs. Evidence argues against the development of CLB tolerance in most patients. Antiseizure medication shortages have been reported by many countries, including the one studied here. Shortages make treatment harder, increase the need for extra clinical appointments, for orientation and medication changes, increase medication errors, decrease adherence, and cause insecurity. A literature review showed scarce evidence of alternatives, with a wide variation in dosage equivalence. A survey of specialists revealed that switch appropriateness was deemed inadequate by the majority, due to risk of seizure worsening and side effects. Clonazepam and nitrazepam were the most used BZDs, but there was great variation for clonazepam dosages (0.25–2 mg, commonly 1 per 10 mg of CLB). Better consensus was obtained for nitrazepam (5 per 10 mg of CLB). Gradual tapering of CLB, with concomitant increase of clonazepam or nitrazepam under close supervision, is advised. It is important to assess tolerability and the need for increased dosage. As CLB is an essential tool in the epilepsy armamentarium, shortages pose great risk to the patients. Governments and society must create mechanisms to prevent shortages of critical and unique medications.
Keywords: Clobazam; Epilepsy; Dosage; Surveys and Questionnaire; Review